Paper withdrawn_202304 A crisis like no other: Disruptions of the Covid-19 pandemic in the neoliberal African higher education era - Ndofirepi, A.; Hungwe, J. P. (South African Journal of Higher Education, 2022)
The Covid-19 pandemic has offered an opportune moment to assess the neoliberal tendencies in (South) African higher education. In critiquing neoliberal tendencies in higher education, this article proffers the thesis that university in (South) Africa perpetuates and entrenches neoliberalism as a Eurocentric canon, thereby shadowing the public good agenda of higher institutions of learning. The dawn of democracy in many African countries ushered in new thinking concerning higher education policy and practice. However, the Covid-19 pandemic has exposed the fact that African higher education has remained tethered to the former colonial powers’ whims, thereby maintaining the dominator-dominated relationship. We argue that the imposed Western-style education has produced an educated élite with Western values and entrepreneurial attitudes that pilot their states on the path to modernity through the capitalisation of knowledge. Subsequently, the Covid-19 pandemic has exposed deep inequalities in relation to access to African higher education. To that end, we conceptualise the predominance of neoliberal philosophy in African higher education as an instrument of keeping the public good idea of the African universities under surveillance. We provide theoretical evidence of how African universities are still suffering from colonisation of the mind decades after the attainment of political independence through complicit or sometimes implicit imbibing and embracing of the Euro-centred neoliberal philosophy under the guise of globalisation. We make a case for (South) African higher education to turn the tide to encompass locally relevant teaching and research with an eye on local needs in the context of Covid-19 pandemic. On the understanding that Covid-19 pandemic affected places differently, we argue that the deep underlying inequalities in African higher education were exposed.